STATUS KEBERSIHAN GIGI DAN MULUT DENGAN GINGIVITIS PADA IBU HAMIL DI PUSKESMAS SIMPANG TIGA ACEH BESAR TAHUN 2022 - Teuku Salfiyadi; Lisa Hanum; Reca Reca; Cut Aja Nuraskin (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
This study aims to determine the relationship between dental and oral hygiene and gingivitis in pregnant women who visit the Simpang Tiga Health Center, Aceh Besar. This research was conducted using an analytical method with a cross-sectional design which was conducted from 5 February to 2 March 2022 at the Simpang Tiga Health Center, Aceh Besar District. The population in this study was the average number of pregnant women in trimesters 1-3 who visited during the last 3 months with a sample of 30 respondents. The study was conducted by examining dental and oral hygiene and examining the respondents for gingivitis. Data analysis using chi-square test statistical test. The results showed that the dental and oral hygiene of pregnant women who visited the Simpang Tiga Public Health Center was in the category of 15 (50.3%) respondents while the next was in the bad category of 13 (43.3%) with 0.016. Dental and oral hygiene of pregnant women has a significant relationship with gingivitis so it is very disturbed by the mother's condition. From these results, it is necessary to increase the understanding of pregnant women in maintaining dental health during pregnancy. Conclusion The understanding of pregnant women about dental and oral health needs to be improved with improved counseling methods so that in the future it is hoped that the community (pregnant women) will increase.